Thermal, chemical and mechanical characterization of Azadirachta indica tree gum - Joy Mathavan, J.; Hassan, Muhammad Hafiz bin (International Journal of Biological Macromolecules, 2024)
Anacardium occidentale (cashew) tree gum is being used in several sectors, including the pharmaceutical sector. This gum has been explored more in the medical field by many previous researchers, but there is a big research gap regarding its thermal and mechanical properties. Therefore, this research is intended to reveal the thermal, chemical, and mechanical characteristics of Anacardium occidentale tree gum. The results obtained in this regard are then compared with certain properties of artificial resins. Thermal analysis is carried out using a thermog ravimetric analyzer, and differential scanning calorimeter, elemental analysis is carried out using a scanning electron microscope and a micro-X-ray fluorescence analyzer; and mechanical tests are carried out using a nano- indentation tester and a universal testing machine. The pH of 4.76 shows that the gum is acidic in nature, and the peaks obtained from thermal analysis demonstrate that it doesn’t have a melting point. The microhardness value, tensile strength, flexural strength, and compressive strength of cashew gum are 218.39 MPa, 1.667 MPa, 3.64 MPa, and 2.667 MPa, respectively. The obtained results show that, Anacardium occidentale tree gum has com parable thermal properties to those of artificial resins and other natural gums.
Keywords: Anacardium occidentale tree gum; μ X-ray fluorescence test; Simultaneous thermal analysis